Evaluasi efektifitas edukasi anemia pada remaja putri melalui permainan flashcard: Studi di SMPN 2 Jabon Kabupaten Sidoarjo - Tri Valda Gilby Renata; Sulistiyani Sulistiyani; Nur Fitri Widya Astuti (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Anemia is a serious global public health problem, especially in adolescents. The incidence of anemia in Sidoarjo Regency is 32.9% and there are 2271 students who are at risk of anemia. Good knowledge of adolescents about anemia, especially nutritional intake, can have an influence on the incidence of anemia and adolecents attitudes about anemia. Researchers designed an interesting and not yet widely used flashcard games.Objectives: The research aims to analyze the differences in knowledge and attitudes of young women before and after providing education about anemia using flashcard games.Method: The method used was a quasy experiment nonequivalent control group design, which was carried out at SMPN 2 Jabon. The sampling technique used stratified random sampling, targeting 84 junior high school students. Data was collected using a questionnaire sheet then processed and analyzed using SPSS (Mann Whitney test).Results: The mean difference in knowledge scores was 42.15 ± 9.764 (control group), 42.85 ± 9,764 (experimental group) and in attitude scores 46.25 ± 5.209 (control group) and 38.75 ± 5.209 (experimental group). The results of the Mann Whitney test are the sig value 0.895 (knowledge) and 0.158 (attitude), so it can be interpreted that there is no difference in the knowledge and attitudes of young women before and after being given anemia education with flashcard games (sig > 0.05).Conclusion: There is no difference in knowledge about anemia and there is no difference in respondents' attitudes regarding anemia.